This fabulous century 1930-1940 - Editors of Time-Life Books (Time-Life Books Alexandria, Va, 1970)
Photographs and illustrations present various aspects of American society during the 1930s and 1940s.
Keywords: History -- 20th century -- United States; Pictorial works; 20th century -- United States